The Development of Furniture Assembly Instruction Based on Augmented-Reality - Hugo Adrian Hartanto; Irena Krishanti Makrie; Violitta Yesmaya; Permana Gustav Halfian (ComTech: Computer, Mathematics and Engineering Applications, 2019)
This research utilized Augmented Reality (AR) technology along with interactive multimedia applications to improve visual guidance and assist nonexpert users in assembling furniture. Rather than paperbased or video instructions, AR enhanced learning and manipulative-interactive approach. This research used the Waterfall model for development. It was divided into a couple of stages. It consisted of specifying the problem and requirements, designing the system, implementing and integrating it, and testing the system. Identifying problems and requirements was conducted through an online questionnaire and related works study. The graphics tool used was 3D Studio Max. Unity3d was used to develop the system with the software library from Qualcomm’s Vuforia for the AR implementation. The results show the mobile application called ARsembly. It serves as the early stage of concept model as it only assists the simple assembly. Through system testing performed by both researchers and end-users, ARsembly is proven to be useful and helpful in learning and performing furniture assembly.